Precessão Livre de Onda Contínua (CWFP) como ferramenta para supressão do sinal de solvente em RMN de alta resolução - Duarte, Claudimar Junker (Universidade Federal de São Carlos, 2011)
The application of Continuous Wave Free Precession (CWFP) method for solvent suppression in high resolution NMR spectroscopy is reported. The applied methodology was based in the use of conventional pulse sequence that use a train of pulses with same phase, intensity and duration, separated by a time interval (Tp) shorter than the longitudinal (T1) and transverse (T2) relaxation times of the sample. After that, it was performed modifications that correspond to the phase alternation of pulses. These modifications allowed to minimize phase anomalies, which result from the refocusing of the magnetization and occur in the 1H spectrum when using the conventional pulse sequence. Through the new sequence, named PA-CWFP, it was possible to suppress solvent signals in several samples with different characteristics and the determination of sucrose content in four different types of grapes (Vitis vinifera), available in the local trade. In addition, the train of pulses with phase alternation was added in two routines 2D experiments: COSY (Correlation Spectroscopy) and HMBC (Heteronuclear Multiple-Bond Correlation Spectroscopy). The results were compared with traditional sequences for solvent suppression and demonstrate the potential of Continuous Wave Free Precession method for experiment of this type.
Continuous wave free precession (cwfp) as tool for solvente suppression in high resolution nmr spectroscopy
Keywords: Química orgânica; Precessão livre de onda Contínua (CWFP); Supressão do sinal do solvente; RMN de 1H em alta resolução; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA